Iman yang Bertumbuh dalam Tindakan: Implikasi Konsep Tabula Rasa dan Pendidikan Ekologi bagi Anak Sekolah Minggu Huria Kristen Batak Protestan - Manalu, Musdodi (IAKN Ambon, 2024)
This article explores the integration between John Locke's concept of tabula rasa and ecological education for Sunday School children in the Huria Kristen Batak Protestan (HKBP) Church. The research aims to investigate how Locke's philosophical concept of the mind as an empty